24.20%‐Efficiency MA‐Free Perovskite Solar Cells Enabled by Siloxane Derivative Interface Engineering. Issue 48 (25th October 2022) - Duan, Yuwei; He, Kun; Yang, Lu; Xu, Jie; Zhao, Wenjing; Liu, Zhike
Abstract: Suppressing defects at the interface between the TiO2 electron transport layer (ETL) and perovskite film is critical for high efficiency and stable perovskite solar cells (PSCs). Herein, a siloxane derivative diethylphosphatoethylsilicic acid (PSiOH) is developed to modify the interface of TiO2 ETL/FA0.83 Cs0.17 PbI3 perovskite. Comprehensive characteristics reveal that silicon hydroxyl (SiOH) in PSiOH can reduce surface defects, improve the electrical properties and optimize the energy band structure of TiO2 by forming a SiOTi bond, while the phosphate bond (PO) in PSiOH can passivate Pb‐related defects on the perovskite bottom surface. Consequently, PSiOH‐modified PSCs yield a remarkable power conversation efficiency of 24.20% and improved air, thermal, or illumination stabilities. This study provides insight into passivation defects at the buried interface for efficient and stable PSCs. Abstract : Herein, a siloxane derivative diethylphosphatoethylsilicic acid (PSiOH) is developed to modify the interface of TiO2 /FA0.83 Cs0.17 PbI3 . Comprehensive characteristics reveal that PSiOH can reduce surface defects, improve electrical properties and optimize energy band structure of TiO2, and passivate Pb‐related defects on the perovskite bottom surface. Consequently, PSiOH‐modified perovskite solar cells (PSCs) yield a remarkable efficiency of 24.20% and improved stability.